2012
DOI: 10.1017/s0305000912000554
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of contrastive pitch accent in six- to eleven-year-old English-speaking children (and adults)

Abstract: Both off-line and on-line comprehension studies suggest not only toddlers and preschoolers, but also older school-age children have trouble interpreting contrast-marking pitch prominence. To test whether children achieve adult-like proficiency in processing contrast-marking prosody during school years, an eye-tracking experiment examined the effect of accent on referential resolution in six- to eleven-year-old children and adults. In all age groups, a prominent accent facilitated the detection of a target in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
54
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 41 publications
9
54
3
Order By: Relevance
“…They also reported that vocal emotion recognition in children develops later than the corresponding linguistic ability. Ito, Bibyk, Wagner, and Speer [58] reported agerelated improvements in interpreting contrastive accent in children aged between 6 and 11 years, however even the 11 year olds showed delayed responses compared to adults. This suggests that it may take many years for children to acquire the pragmatic meaning of pitch accent.…”
Section: Discussionmentioning
confidence: 97%
“…They also reported that vocal emotion recognition in children develops later than the corresponding linguistic ability. Ito, Bibyk, Wagner, and Speer [58] reported agerelated improvements in interpreting contrastive accent in children aged between 6 and 11 years, however even the 11 year olds showed delayed responses compared to adults. This suggests that it may take many years for children to acquire the pragmatic meaning of pitch accent.…”
Section: Discussionmentioning
confidence: 97%
“…The previous research introduced a puzzle: young children are able to rapidly use contrastive accents to make online predictions about upcoming referents (Ito et al, 2014) but they fail to use contrastive accents in offline judgment (Cruttenden, 1985;Wells et al, 2004). This discrepancy could reflect task demands: the previous offline tasks required participants to make inferences about an unknown context.…”
Section: Discussionmentioning
confidence: 99%
“…While it is clear that children are able to use contrastive accents for making local predictions (Ito, Bibyk, Wagner, & Speer, 2014;Ito, Jincho, Minai, Yamane, & Mazuka, 2012;Sekerina & Trueswell, 2012), we do not know how these accents affect their subsequent representation of the discourse, or their ability to remember it. The present study explores this question in 5-year-old children.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations